Characterisation of the deubiquitinating enzyme USP4 - Indrayudha, Peni (2018)
Ubiquitin Specific Protease (USP) 4 is a deubiquitinating enzyme (DUB) which is an important regulator of different cellular pathways, such as Wnt signalling, and A2A-adenosine receptor signalling. USP4 can remove ubiquitin from RIP1, PDK-1, and Ro52, interacts with SART3 at the spliceosome and regulates TNFα and IL-1β in cancer. The full-length structure of USP4 remains to be investigated. The structure of USP4 consists of an N-terminal DUSP (domain in USPs), two Ubl (Ubiquitin-like) domains, and two subdomains that form one catalytic domain. Only the structure of the DUSP-Ubl and catalytic core lacking the Ubl2 domain has so far been determined. Six constructs were cloned based on the USP4 domain architecture to investigate the structure and function of individual USP4 domains. The constructs were tested by enzymatic activity assays. Site directed mutagenesis of the catalytic site, namely mutants H881N and C311S were generated to form complexes with Ubiquitin, Ubiquitin-GGG, diubiquitin and diubiquitin-L73X. The 6 constructs were: USP4FL (full-length), USP4htt (head-to-tail), USP4httΔUbl2, USP4C1C2 (catalytic core), USP4ΔDU (lacking the N-terminal DUSP-Ubl domains), and USP4DU (N-terminal domains). Expression and purification was generally done by the Ni column and gel filtration method. Some further purification was performed by anion exchange chromatography. Enzymatic activity assays were conducted using Ub-AMC (Ubiquitin-7-amido-4-methylcoumarin) as the fluorogenic substrate. The mutagenesis was done by exchange of Histidine (H) to Asparagine (N) and Cysteine (C) to Serine (S) in the catalytic triad and protein complexes were created by combining the mutants with Ubiquitin variants. These complexes were set up for crystallization trials. The protein complexes of active site mutant USP4 with Ubiquitin variants were analysed using ESI-MS and ITC. All the protein constructs were successfully cloned, expressed and purified. USP4httΔUbl2 was well expressed with high yields and USP4htt needed optimisation to increase the yield. Enzymatic activity assays showed that the highest specific activity was obtained for USP4C1C2 whereas USP4htt was the lowest. Some protein crystals were obtained from complexes of active site mutant USP4 with Ubiquitin variants. Only the complex USPFL-H881N with diubiquitin produced crystals that diffracted to 3 Å resolution although the structure has not yet been solved. Binding interaction between various active site mutant constructs of USP4-C311S with ubiquitin variants showed that Ubiquitin and Ub-GGG have the highest affinity for USP4C1C2-C311S. Diubiquitin had the highest affinity for USP4FL-C311S. Together these data provide novel insights into USP4 structure and ubiquitin recognition.